PENGARUH INFLASI, KURS DOLAR AS, DAN SUKU BUNGA (BI), TERHADAP PENENTUAN HARGA EMAS - Nurulhuda, Elly Soraya; Kosasih, Kosasih (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Investing gold is one of the right choices to avoid losses due to the economy that is sometimes uncertain, gold investment is a low-risk investment instrument, gold is a good hedge option because gold is not affected by inflation or zero inflation. This study aims to determine the effect of inflation, US Dollar Exchange Rates, and Interest Rates (BI), on the Gold Price. The sample used in this study is the company PT Antam Tbk, 2014-2018, where the company is a company engaged in the sale of gold and other metals, as well as a company that sets the price of gold in Indonesia. This study uses a quantitative approach. The data used are secondary data from 2014-2018. The data analysis technique used is time-series data with multiple linear regression methods of panel data using Eviews 9. Based on the analysis found that partially (t-test) inflation has a significant positive effect on the price of gold, while the US dollar exchange rate has a positive effect not significant to the price of gold. And simultaneously (Test F) Interest Rate (BI) has a significant negative effect on the price of gold.